Analysis of Asset Valuation on the Amount of Loans at PT. Pegadaian (Persero) Baubau Branch: Analisis Penilaian Aset Terhadap Jumlah Pinjaman Pada Pt. Pegadaian (Persero) Cabang Baubau - Sarsina, Wa Ode; I Wayan Sujana (Jurnal Riseta Soshum, 2025)
The purpose of this study was to determine and analyze the assessment of gold jewelry assets against the amount of loans provided by PT. Pegadaian (Persero) Baubau Branch. This type of research is qualitative, data collection in this study was carried out in several stages, namely: 1) Observation; 2) Interview; and 3) Documentation. The data analysis method used is based on the analysis steps initiated by Miles and Huberman, consisting of several parts, namely: 1) Data Collection; 2) Data Reduction; and 3) Data Display; and 4) Conclusion Drawing and Verification. The results of this study found that in the implementation of the assessment or appraisal of gold jewelry pawns to determine the amount of loans at the Baubau Branch of Pegadaian, the assessment of gold jewelry was carried out by considering several main factors, namely carat content, net weight, physical condition, and the market price of gold jewelry. The authenticity factor of gold jewelry does not affect the estimated value, but the authenticity of gold is the main basis for determining the value of assets before entering the estimated value determination stage. The implementation of the assessment carried out has good and precise standards in accordance with the provisions set by the head office. The estimated value then becomes the basis for determining the amount of the loan, which is calculated by multiplying the estimated value of the gold by the percentage of the loan determined by the pawnshop institution